Western Europe in Transition : Impact of Opening Up Eastern Europe. (International Monetary Fund, 1997)
This paper examines the impact of the opening up of Eastern Europe and the Former Soviet Union on Western Europe. The analysis suggests that given reasonable (yet necessarily imprecise) assumptions on the likely developments in the previously centrally planned economies (PCPEs) over the next ten years, West European capital markets are likely to experience only a mild squeeze from their concerted efforts to provide external financing to the East. Most macroeconomic aggregates are likely to suffer shocks significantly smaller than would be expected from a typical business cycle.